2018
DOI: 10.1177/0886260518779067
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combining Business Training, Microfinance, and Support Group Participation on Economic Status and Intimate Partner Violence in an Unplanned Settlement of Nairobi, Kenya

Abstract: Intimate partner violence (IPV) has myriad negative health and economic consequences for women and families. We hypothesized that empowering women through a combination of formal business training, microfinance, and IPV support groups would decrease IPV and improve women's economic status. The study included adult female survivors of severe IPV. Women living in Korogocho received the intervention and women in Dandora served as a standard of care (SOC) group, but received the intervention at the end of the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…While the economic status of the family was a key factor driving women not to report, the survivor's perspective on the decision to accept financial reparations is critically important for understanding this common cultural practice. Addressing women's economic empowerment can address these challenges to an extent but may not be sufficient to prevent sexual violence and remove barriers to post-rape assistance (Sarnquist et al, 2018). Finding strategies to combat this practice would also reduce the likelihood of repeat offenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the economic status of the family was a key factor driving women not to report, the survivor's perspective on the decision to accept financial reparations is critically important for understanding this common cultural practice. Addressing women's economic empowerment can address these challenges to an extent but may not be sufficient to prevent sexual violence and remove barriers to post-rape assistance (Sarnquist et al, 2018). Finding strategies to combat this practice would also reduce the likelihood of repeat offenses.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing women’s economic empowerment may address these challenges to an extent, but will not be sufficient to remove barriers to post-rape assistance and ultimately break the cycle of sexual violence that causes so much destruction (Sarnquist et al, 2018). Social support is important for women’s economic survival and as a resource for survivors in their own right (Bourey et al, 2015; Sarnquist et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A cluster randomized trial of IMAGE (Intervention with Microfinance for AIDS and Gender Equity), which integrates microfinance with a gender and HIV curriculum, showed a 55% reduction in past-year physical or sexual IPV in South Africa (Pronyk et al, 2006). Reductions in IPV have also been observed in studies of economic empowerment programs in diverse settings worldwide (Glass et al, 2017; Kapiga et al, 2019; Sarnquist et al, 2021) and in Bangladesh (Schuler et al, 1996). Yet, some studies have found that women’s participation in economic empowerment interventions can, in fact, heighten their risk of IPV (Bhuiya et al, 2003; Dalal et al, 2013; Schuler et al, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…For instance, the successful IMAGE intervention in South Africa combined skills building and empowerment training with microcredit (Ellsberg et al, 2015; García-Moreno et al, 2014; Kim et al, 2007). Similarly, the Mashinani program in Kenya found that skill development and business planning, in addition to support groups for survivors of violence, led to reductions in IPV (Sarnquist et al, 2021). Our findings also underscore the need to more granularly capture women’s true involvement and participation throughout the entire microcredit process to more fully and accurately describe its ability to bring about, or fail to bring about, empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of clusters, short duration of follow-up, and biased reporting were several limitations of the study. The next intervention (Mashinani) by Clea Sarnquist was a woman empowering program through a combination of formal business training, microfinance, and IPV reduction activities ( 31 ). Women aged 18 years or older who were victims of DV were included.…”
Section: Resultsmentioning
confidence: 99%